The flavonoid quercetin reduces cell migration and increases NIS and E-cadherin mRNA in the human thyroid cancer cell line BCPAP. (1st June 2021) - Gonçalves, Carlos Frederico Lima; Hecht, Fabio; Cazarin, Juliana; Fortunato, Rodrigo Soares; Vaisman, Mario; Carvalho, Denise Pires de; Ferreira, Andrea Claudia Freitas
Abstract: Thyroid cancer is the most frequent cancer of the endocrine system. Most patients are treated with thyroidectomy followed by radioiodine therapy. However, in part of the patients, a reduction of the sodium-iodide symporter (NIS) occurs, rendering radioiodine therapy ineffective. Moreover, epithelial–mesenchymal transition (EMT) may occur, leading to more aggressive and invasive features. Herein, we evaluated the effect of the flavonoid quercetin on EMT and NIS expression in BCPAP, a papillary thyroid carcinoma cell line. BCPAP was treated with 100 μM quercetin for 24 h and cell viability, apoptosis, EMT markers and NIS were evaluated. Quercetin decreased cell viability by enhancing apoptosis. The flavonoid also reduced matrix metalloproteinase 9 and increased E-cadherin mRNA levels, inhibiting BCPAP adhesion and migration. Additionally, quercetin increased NIS expression and function. Thus, our results suggest that quercetin could be useful as adjuvant in thyroid cancer therapy, inducing apoptosis, reducing invasion and increasing the efficacy of radioiodine therapy. Graphical abstract: Image 1 Highlights: Thyroid cancer is the most common cancer of endocrine system. Quercetin induced thyroid cancer cell line BCPAP apoptosis, reducing cell number. Cell adhesion, migration and some epithelial–mesenchymal transition markers were reduced. Quercetin increased sodium-iodide symporter mRNA levels and radioiodide uptake. Quercetin could be useful as adjuvant in the management of thyroid cancer.